2017
DOI: 10.21608/jpp.2017.37824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Maturity Stages on Fruit Yield and Essential Oil Content of Some Apiaceae Family Plants A: Anise (Pimpinella anisum, L.)

Abstract: This study investigated the effects of harvesting at different plant maturation stages on the fruit and essential oil yield as well as its compositions of anise. It was carried out at El-Baramoon Research Farm, Mansoura Horticulture Research Station, HRI, ARC, Egypt, during the winter seasons of 2013/2014 and 2014/2015. The plants were harvested at eight different fruit development stages and determinations were made of the yields of fruit , germination percentage the thousand fruit weight (seed index), the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The size and weight of harvested makhwaen fruits of different maturity stages were measured ( Table 2). Fruit sizes and weight ranged from ≈3.4-3.7 mm and 0.016-0.034 g, and is consistent with the report from Suksathan et al [21] who reported that the size of fruit was about 3-4 mm and 0.010-0.030 g. Harvest time was important for the accumulation of chemical substances in essential oils, as immature harvesting may cause the yield and accumulation of essential substances to be lower [32]. Variation of fruit colour from 15-60 days after initial fruiting are varied ( Figure 1).…”
Section: Fruit Size Weight and Coloursupporting
confidence: 90%
“…The size and weight of harvested makhwaen fruits of different maturity stages were measured ( Table 2). Fruit sizes and weight ranged from ≈3.4-3.7 mm and 0.016-0.034 g, and is consistent with the report from Suksathan et al [21] who reported that the size of fruit was about 3-4 mm and 0.010-0.030 g. Harvest time was important for the accumulation of chemical substances in essential oils, as immature harvesting may cause the yield and accumulation of essential substances to be lower [32]. Variation of fruit colour from 15-60 days after initial fruiting are varied ( Figure 1).…”
Section: Fruit Size Weight and Coloursupporting
confidence: 90%
“…The origin of anise is not exactly known but it has been a commonly found in Egypt, Syria, Cyprus, Greece, Crete Islands and Turkey. The seeds are used in medicine, pharmaceutics, perfumery and cosmetic industries (El-Gamal and Ahmed, 2017;Meena et al, 2015;Faravani et al, 2013;Nabizadeh et al, 2012 andCeylan, 1997). The anise fruit contains essential oil from 1.5 to 4.0% (Radosav et al, 2012) and main component of essential oil is trans-anethole (Ceylan, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of anise is not exactly known but it has been a commonly found in Egypt, Syria, Cyprus, Greece, Crete Islands and Turkey. The seeds are utilized in medicine, pharmaceutics, perfumery and cosmetic industries (Nabizadeh et al, 2012 andEl-Gamal andAhmed, 2017). The main active component of essential oil is trans-anethole.…”
Section: Introductionmentioning
confidence: 99%